Managing crises before they happen what every executive and manager needs to know about crisis management - Mitroff, Ian I. (AMACOM, 2000)
This guide offers a best practices model for crisis management. It aims to help readers better understand why crises occur and what can be done to manage them more effectively before, during and after they occur. There is a strong emphasis on ethics and personal accountability.